2023
DOI: 10.1037/pst0000469
|View full text |Cite
|
Sign up to set email alerts
|

V-episodes in the alliance: A single-case application of multiple methods to identify rupture repair.

Abstract: The therapeutic alliance has been consistently found to be a robust predictor of therapeutic outcome across various modalities of psychotherapy. Alliance ruptures are thought to occur commonly within each therapeutic dyad and, if left unresolved, are associated with premature termination and worsened psychotherapy outcome. Research efforts have identified V-shaped shifts in the alliance, characterized by a high-low-high pattern of postsession alliance scores, as a meaningful method of operationalizing rupture-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The goal of the present study was to assess whether session-by-session changes in self-reported alliance scores can serve as a measure of ruptures in the therapeutic alliance. In line with our hypothesis and Lipner et al (2023), sessions with a drop in the alliance rating based on a case-sensitive method differed from randomly selected sessions of the same treatment phase by presenting more rupture markers and a higher impact of ruptures. Case-sensitive methods take reporter variability in alliance ratings into account when assessing the presence of ruptures and may actually represent a parsimonious tool to identify ruptures in psychotherapy sessions to provide therapists with meaningful feedback about when they occur.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The goal of the present study was to assess whether session-by-session changes in self-reported alliance scores can serve as a measure of ruptures in the therapeutic alliance. In line with our hypothesis and Lipner et al (2023), sessions with a drop in the alliance rating based on a case-sensitive method differed from randomly selected sessions of the same treatment phase by presenting more rupture markers and a higher impact of ruptures. Case-sensitive methods take reporter variability in alliance ratings into account when assessing the presence of ruptures and may actually represent a parsimonious tool to identify ruptures in psychotherapy sessions to provide therapists with meaningful feedback about when they occur.…”
Section: Discussionsupporting
confidence: 73%
“…Alliance ruptures can be measured in various ways: (a) by means of observer-based ratings of what happens in the therapy sessions (e.g., Rupture Resolution Rating System [3RS]; Eubanks et al, 2015), (b) by directly asking the patient and/or the therapist questions about the occurrence of a rupture in the session, or (c) by identifying declines in self-reported alliance ratings based on some criterion and interpreting these drops as indirect measures of ruptures (Eubanks et al, 2018). A review of rupture identification methodologies based on alliance self-report measures indicated a wide range in the frequency of ruptures across studies (Lipner et al, 2023), likely reflecting the lack of consistency between various methods. Eubanks-Carter et al (2012) differentiated between two methods to identify rupture sessions using indirect assessment: the criterion-based and the case-sensitive method.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moderator analyses found that this association between rupture and repair and outcome was not related to how rupture and repair were operationalized (e.g., direct vs. indirect assessment). In addition, recent research shows that these V-shaped patterns are associated with observer-rated within-session rupture processes (Lipner et al, 2023). Therefore, V-shaped patterns of alliance ratings are indicators of a rupture-and-repair process, which is associated with client improvement.…”
Section: Between-person Working Alliance Strengthmentioning
confidence: 99%